2016 European Intelligence and Security Informatics Conference (EISIC) 2016
DOI: 10.1109/eisic.2016.044
|View full text |Cite
|
Sign up to set email alerts
|

On Privacy and Security Challenges in Smart Connected Homes

Abstract: -Smart homes have become increasingly popular for IoT products and services with a lot of promises for improving the quality of life of individuals. Nevertheless, the heterogeneous, dynamic, and Internet-connected nature of this environment adds new concerns as private data becomes accessible, often without the householders' awareness. This accessibility alongside with the rising risks of data security and privacy breaches, makes smart home security a critical topic that deserves scrutiny. In this paper, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(85 citation statements)
references
References 18 publications
0
80
1
4
Order By: Relevance
“…As their popularity increases, Internet of Things devices present an increasing threat to the security of the Internet as a whole [17,23,44] as well as to the privacy of individual end-users [4,9,14]. Yet, because these devices enter homes as "smarter" versions of already-existing appliances (e.g., TVs, light bulbs, and locks), users are often unaware of the risks they pose [32].…”
Section: Related Workmentioning
confidence: 99%
“…As their popularity increases, Internet of Things devices present an increasing threat to the security of the Internet as a whole [17,23,44] as well as to the privacy of individual end-users [4,9,14]. Yet, because these devices enter homes as "smarter" versions of already-existing appliances (e.g., TVs, light bulbs, and locks), users are often unaware of the risks they pose [32].…”
Section: Related Workmentioning
confidence: 99%
“…Security Vulnerabilities: Recent works have outlined security threats to SHSs [10,23,25].These threats focus on three SHSs components: communication protocols, devices, and apps. Attackers may exploit implementation flaws in communication protocols to leak sensitive information from devices [13,21,26] via information extracted from network packets [1,5,16]. Fernandes et al reported several design flaws in SHSs [11].…”
Section: Related Workmentioning
confidence: 99%
“…Since it becomes unnecessary for devices to install a communication function and a security function (Joseph Bugeja et al, 2016) for connecting to the Internet, it is also possible to reduce the cost for making the device IoT.…”
Section: Introduction Of Iot Devicementioning
confidence: 99%